Highly Reliable 90-nm Logic Multitime Programmable NVM Cells Using Novel Work-Function-Engineered Tunneling Devices - Paulsen, Ron (IEEE Transactions on Electron Devices, 2007)
A highly reliable embedded logic multitime-programmable nonvolatile memory (NVM) has been developed in a standard 90-nm logic process with no process changes and a zero-mask adder. By using a novel work-function-engineered tunneling device and 70-Aring tunneling oxide, an excellent endurance of more than 500 k cycles has been achieved. Reliability of the NVM is evaluated against the traditional tunneling device, and a model is proposed to explain the observed reliability differences. Process manufacturability on retention has also been demonstrated over process variations on the thickness of silicide-blocking layers.